Therapeutic modulation methods of gut microbiota and gut-liver axis - Coskun, Ayfer Beyaz; Celep, Adviye Gulcin Sagdicoglu (Taylor & Francis Inc, 2022)
Liver diseases are considered global health problems that cause more than 1 million deaths each year. Due to the increase in the prevalence of liver diseases worldwide, studies on different treatment methods have increased. Some of these methods is diagnostic and therapeutic applications based on the examination of the intestinal and intestinal microbiota. In this study, research articles, systematic review and review in the literature were examined in order to determine gut-liver axis relationship and treatment methods for liver diseases with gut modulation methods. Studies related to the subject have been searched in Google Scholar and Pubmed databases. The keywords liver disease and gut-liver axis and microbiota and gut modulation methods or probiotic or prebiotic or symbiotic or antibiotic or bile acid regulation or adsorbent or fecal microbiota transplantation were used in the searches. Improvements have been achieved in biomarkers of liver diseases by providing intestinal modulation with probiotic, prebiotic, symbiotic, antibiotic and adsorbents applications, bile acid regulation and fecal microbiota transplantation. In the results of experimental and clinical studies, it was seen that the therapeutic potential of the treatments performed by applying probiotics, prebiotics and symbiotics was higher.
Keywords: Gut modulation methods; liver disease; probiotic; prebiotic; symbiotic